Ekonomiczne przesłanki rozwoju usług produkcyjnych dla rolnictwa - Wojciechowska-Ratajczak, Bogumiła (Wydział Prawa i Administracji UAM, 1983)
The article is an attempt at defining economic foundations of the developement of productive services in Polish agriculture. The results of deduction were empirically verified on the grounds of a statistical analysis of character and dynamics of structural changes of the system of productive services in the years of 1970 - 1980 and of their compatibility to preferences of individual and collective farms. Results of the examination (proved that directions of changes in the sphere of productive services in our agriculture of the pariod in question were in general in keeping with regularities in that branch. Yet, the scale of those changes was such that it could not effect any substantial, socially needed transformat ions of the traditional structure of services. Further improvement in a structure (subjects and objects) of the system of productive services of agriculture should be, above all concentrated in the direction of rapid developement of services both ante- and post-productive as well as of off-farm service units.
Economic foundations of the developement of productive services for agriculture